Sintesis Fenil Sinamat dan 4-Fenilkroman-2-on dan Uji Sitotoksisitas Terhadap Sel Kanker Serviks HeLa - TENI ERNAWATI; DILA FAIRUSI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Cinnamic acid is a derivative of methyl cinnamate; it is included in the shikimic acid pathway derivatives. Cinnamic acid and its natural analogue are known as a cancer treatment for several centuries.Synthesis of phenyl cinnamic and 4-phenilkroman-2-on derived from methyl cinnamate had been done by using acid as a catalyst. Methyl cinnamic was first converted into cinnamic acid via hydrolysis reaction with alkaline. After that, cinnamic acid was chlorinated by using thionyl chloride and phenol reagent to produce fenil-sinamat. Esterification reaction was carried out by using an acid catalyst p-toluen sulfonic acid and phenol resulting 4-phenilkroman-2-on. We obtained the products for the synthesis of cinnamic acid, cinnamic phenyl and 4-fenilkroman-2-on, with yields respectively of 83.6%, 14.71%, and 16.18%.Cytotoxicity test using the brine shrimp lethality test (BSLT) was conducted on both cinnamic phenyl compound and 4-phenilkroman-2-on compound. LC50 values obtained for both compounds respectively were 223.87 ppm and 112.72 ppm. The results of MTT cytotoxicity assay method for cervical cancer HeLa cells (ATCC CCL2) using phenyl cinnamic and 4-phenilkroman-2-on were found that the percentage of inhibition obtained is over 50%.